2022
DOI: 10.4018/978-1-7998-6829-3.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Role of Artificial Intelligence in K12

Abstract: The purpose of this study is to explore AI (artificial intelligence)-enhanced teaching and learning in future educational development. The chapter is a representation of whether the future of online platforms will highly depend on AI or not. The study identified how students are affected by technology-enhanced AI as a future online platform. The study consists of qualitative research methodology approach where literature review is conducted to determine the future of online platforms with the help of robotic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Few respondents used mobile devices for gaming and other purposes. These results are similar to Ozan et al (2015), Mtebe and Raisamo (2014) and Nadi et al (2023), as they reported that most students use mobile devices for academic purposes. Furthermore, among various academic purposes, the main academic purposes were checking and sending e-mails, accessing search engines, completing assignments, research work activities and training and selflearning.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Few respondents used mobile devices for gaming and other purposes. These results are similar to Ozan et al (2015), Mtebe and Raisamo (2014) and Nadi et al (2023), as they reported that most students use mobile devices for academic purposes. Furthermore, among various academic purposes, the main academic purposes were checking and sending e-mails, accessing search engines, completing assignments, research work activities and training and selflearning.…”
Section: Discussionsupporting
confidence: 91%
“…Mobile devices such as tablets and smartphones have been adopted rapidly and have outpaced desktop computers (Nadi et al , 2023). Combined with improved broadcasting systems and reduced device sizes and prices, usage regularity and percentages have tremendously increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure effective implementation, teachers should clearly understand the student's needs and learning objectives and be involved in the design process of chatbots. Additionally, teachers should be well-versed in the features and capabilities of chatbots and understand how to use them to promote learning in their classrooms (Nadi et al, 2022). Teacher training and support should be incorporated into any implementation plan for using chatbots in education to maximise the effectiveness of their use.…”
Section: Implications For Practicementioning
confidence: 99%
“…The IoT stands poised to realize this vision and address pertinent challenges, creating a superior alternative to traditional elearning systems [26][27][28][29][30]. However, it is worth noting that developing nations such as Saudi Arabia have yet to fully embrace the IoT within their educational infrastructures [31][32][33][34], and technologies such as e-learning [35], m-learning [36], ubiquitous learning [37], and virtual teaching/learning methods [38] have not brought about the expected transformative impact in higher education. This study aims to establish a robust strategy to enhance the integration of the IoT within HEIs, particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%